Hubungan Senam Hamil dengan Lama Tidur Ibu Hamil Trimester III di Puskesmas Putri Ayu Kota Jambi - Sri Maharani (Universitas Baiturrahim, 2021)
Pregnancy is a period that is eagerly awaited by mothers. In conditions of pregnancy there are hormonal and physiological changes. The changes that occur are expected to be carried out by pregnant women in order to have a comfortable pregnancy. Sleep disturbance is one of the complaints that occurs during pregnancy, the complaint is caused by various physiological, hormonal, vascular and metabolic changes. Empirical studies show that up to 25% of pregnant women report significant sleep disturbances in the first trimester, with rates rising to 75% in the first trimester. third trimester. Overcoming sleep disorders during pregnancy can be done in various ways in order to stabilize good sleep quality, such as determining a good and comfortable sleeping position while sleeping, basic relaxation exercises, one of which is pregnancy exercise. This study aims to determine the relationship between pregnancy exercise and sleep duration of pregnant women. Quantitative research design. The subjects in this study were pregnant women in their third trimester at Puskesmas Putri Ayu Jambi City. The subjects of the study were seen the length of sleep for pregnant women before doing pregnancy exercise and the length of sleep for pregnant women after participating in pregnancy exercise classes. The research was conducted at the Putri Ayu Health Center, Jambi City. The collected data will be analyzed univariately. It is hoped that the results of this study can be used as a source of information for pregnant women about physiological changes during pregnancy and can overcome complaints of difficulty sleeping by doing pregnancy exercise.Keywords: exercise for pregnancy, pregnant women, sleep duration